Nitrite-Oxidizing Bacteria Community Composition and Diversity Are Influenced by Fertilizer Regimes, but Are Independent of the Soil Aggregate in Acidic Subtropical Red Soil - Han, Shun; Li, Xiang; Luo, Xuesong; Wen, Shilin; Chen, Wenli; Huang, Qiaoyun (Frontiers in Microbiology, 2018)
Nitrification is the two-step aerobic oxidation of ammonia to nitrate via nitrite in the nitrogen-cycle on earth. However, very limited information is available on how fertilizer regimes affect the distribution of nitrite oxidizers, which are involved in the second step of nitrification, across aggregate size classes in soil. In this study, the community compositions of nitrite oxidizers (Nitrobacter and Nitrospira) were characterized from a red soil amended with four types of fertilizer regimes over a 26-year fertilization experiment, including control without fertilizer (CK), swine manure (M), chemical fertilization (NPK), and chemical/organic combined fertilization (MNPK). Our results showed that the addition of M and NPK significantly decreased Nitrobacter Shannon and Chao1 index, while M and MNPK remarkably increased Nitrospira Shannon and Chao1 index, and NPK considerably decreased Nitrospira Shannon and Chao1 index, with the greatest diversity achieved in soils amended with MNPK. However, the soil aggregate fractions had no impact on that alpha-diversity of Nitrobacter and Nitrospira under the fertilizer treatment. Soil carbon, nitrogen and phosphorus in the soil had a significant correlation with Nitrospira Shannon and Chao1 diversity index, while total potassium only had a significant correlation with Nitrospira Shannon diversity index. However, all of them had no significant correlation with Nitrobacter Shannon and Chao1 diversity index. The resistance indices for alpha-diversity indexes (Shannon and Chao1) of Nitrobacter were higher than those of Nitrospira in response to the fertilization regimes. Manure fertilizer is important in enhancing the Nitrospira Shannon and Chao1 index resistance. Principal co-ordinate analysis revealed that Nitrobacter- and Nitrospira-like NOB communities under four fertilizer regimes were differentiated from each other, but soil aggregate fractions had less effect on the nitrite oxidizers community. Redundancy analysis and a Mantel test indicated that soil nitrogen, carbon, phosphorus, and available potassium content were important environmental attributes that control the Nitrobacter- and Nitrospira-like NOB community structure across different fertilization treatments under aggregate levels in the red soil. In general, nitrite-oxidizing bacteria community composition and alpha-diversity are depending on fertilizer regimes, but independent of the soil aggregate.